The validation of a heuristic toolkit for augmented reality: the derby dozen - Derby, Jessyca L.; Aros, Michelle; Chaparro, Barbara S. (Frontiers in Virtual Reality, 2025)
Augmented Reality (AR) technologies hold tremendous potential across various domains, yet their inconsistent design and lack of standardized user experience (UX) pose significant challenges. This inconsistency hinders user acceptance and adoption and impacts application design efficiency. This study describes the development of a validated UX heuristic checklist for evaluating AR applications and devices. Building upon previous work, this research expands upon this checklist through expert feedback, validation with heuristic evaluations, and user tests with five diverse AR applications and devices. The checklist was refined to 12 heuristics and 109 items and integrated into a single auto-scored Excel spreadsheet toolkit. This validated toolkit, named the Derby Dozen, empowers practitioners to evaluate AR experiences, quantify results, and ultimately inform better design practices, promoting greater usability and user satisfaction.